FORMATION OF SYSTEMATIC KNOWLEDGE IN SCIENCE STUDENTS IN HIGHER EDUCATION (Revista Inclusiones, 2020)
The study deals with the main issues of developing systematic knowledge in students within higher education and provides possible solutions. A scheme of systematic approach stages is proposed. Particular attention is given to examples from pedagogical practice.